The mortality of Royal Naval submariners 1960-89. Issue 3 (March 1997) - Inskip, H; Snee, M; Styles, L
Abstract : OBJECTIVES: To examine the mortality pattern of submariners in the Royal Navy to assess the long term effects on health of serving in submarines. Any specific cause of death which was increased was considered in advance to be of interest, but attention focused particularly on cancer mortality. METHOD: A mortality follow up study: 15 138 submariners who had conducted their first submarine training between 1960 and 1979 were followed up through their time in the Navy and into civilian life, up to the end of 1989. The main outcome measures were the numbers of deaths and standardised mortality ratios (SMRs) which indicate whether the mortality from all causes and specific causes, particularly cancers, exceeds that in men in England and Wales. RESULTS: Mortality in submariners was lower than that for men in England and Wales with an all cause SMR of 86; this was comparable with that found in other studies of armed forces personnel. Cancer mortality was particularly low with an SMR of 69 and there was no particular cancer site which showed an excess. Increased mortality from digestive diseases was found, the excess being attributable to cirrhosis of the liver, which had an SMR of 221 based on 12 deaths, alcohol being a contributory factor in eight. Deaths from accidents and violence were also higher than expected with an SMR of 115, but this was due to high levels of accidents occurring after discharge from the Navy. There was no apparent trend in mortality with time since starting submarine work. Likewise there was no pattern by calendar period, although the excess of cirrhosis of the liver was confined to the period 1970-9. CONCLUSION: The submariners seemed to be a healthy group with low mortality overall. Working in submarines was not associated with any increased cancer mortality. Excess deaths from cirrhosis of the liver, and from accidents and violence after leaving the Navy, were of some concern but they cannot be attributed directly to the submarine environment.